Metal–Organic Frameworks as Biomimetic Catalysts. Issue 1 (18th October 2013) - Gu, Zhi‐Yuan; Park, Jihye; Raiff, Aaron; Wei, Zhangwen; Zhou, Hong‐Cai
Abstract In this Minireview, we have summarized the recent progress of biomimetic catalysis in the field of metal‐organic frameworks (MOFs) with a focus on the implantation of biomimetic active sites into a stable MOF. In addition, the potential of creating highly selective catalytic pockets and diffusion‐favored hierarchical structures in MOFs has also been explored. Furthermore, we have highlighted the achievements of MOF catalysts in the applications as mimics of peroxidase, cytochromes P450, hemoglobin, and photosynthetic systems.